Donors With Immune Thrombocytopenia: Do They Pose a Risk to Transplant Recipients?. Issue 3 (9th December 2016) - Trotter, P. B.; Robb, M.; Summers, D.; Watson, C. J. E.; Clatworthy, M.; Bradley, J. A.; Hill, Q. A.; Neuberger, J.
Abstract : Transplant‐mediated alloimmune thrombocytopenia (TMAT) from donors with immune thrombocytopenia (ITP) can result in significant bleeding complications in the recipient. The risk to a recipient of TMAT if they receive an organ from a donor with ITP is unknown. The outcomes of recipients of organs from deceased donors with ITP recorded in the UK Transplant Registry between 2000 and 2015 were reviewed. Twenty‐one deceased organ donors had a predonation diagnosis of ITP. These donors were significantly more likely to have died from intracranial hemorrhage than were all other deceased organ donors (85% vs. 57%, p < 0.001). Organs from donors with ITP resulted in 49 organ transplants (31 kidney, 14 liver, four heart), with only one case of TMAT, which occurred in a liver transplant recipient and resulted in death from bleeding complications 18 days posttransplantation. The recipient of a kidney from the same organ donor was not affected. Unadjusted 5‐year patient and graft survival was significantly worse for liver transplant recipients from donors with ITP compared with liver transplant recipients from donors without ITP (64% vs. 85%, p = 0.012). Organs from donors with ITP may be considered for transplantation, but livers should be used with caution. Abstract : Donors with immune thrombocytopenia may cause transplant‐mediated alloimmune thrombocytopenia in their recipients.